Introduction to Sociology - Vu, Xuan Doan (Khoa Quốc tế, ĐHQGHN, 2020)
This introductory course provides an overview of the fundamental concepts and basic principles in sociology: investigating social behavior, culture, institutions, social interaction and social change.